Characterizing white matter fiber orientation effects on multi-parametric quantitative BOLD assessment of oxygen extraction fraction. Issue 4 (April 2020) - Kaczmarz, Stephan; Göttler, Jens; Zimmer, Claus; Hyder, Fahmeed; Preibisch, Christine
Relative oxygen extraction fraction (rOEF) is a fundamental indicator of cerebral metabolic function. An easily applicable method for magnetic resonance imaging (MRI) based rOEF mapping is the multi-parametric quantitative blood oxygenation level dependent (mq-BOLD) approach with separate acquisitions of transverse relaxation times  T 2 * and T2 and dynamic susceptibility contrast (DSC) based relative cerebral blood volume (rCBV). Given that transverse relaxation and rCBV in white matter (WM) strongly depend on nerve fiber orientation, mq-BOLD derived rOEF is expected to be affected as well. To investigate fiber orientation related rOEF artefacts, we present a methodological study characterizing anisotropy effects of WM as measured by diffusion tensor imaging (DTI) on mq-BOLD in 30 healthy volunteers. Using a 3T clinical MRI-scanner, we performed a comprehensive correlation of all parameters (  T 2 *, T2, R 2 ', rCBV, rOEF, whereR 2 ' =1/  T 2 * –1/T2 ) with DTI-derived fiber orientation towards the main magnetic field (B0 ). Our results confirm strong dependencies of transverse relaxation and rCBV on the nerve fiber orientation towards B0, with anisotropy-driven variations up to 37%. Comparably weak orientation-dependent variations of mq-BOLD derived rOEF (3.8%) demonstrate partially counteracting influences ofR 2 ' and rCBV effects, possibly suggesting applicability of rOEF as an oxygenation sensitive biomarker. However, unresolved issues warrant caution when applying mq-BOLD to WM.